Two new orchid bees of the subgenus Euglossella from Peru (Hymenoptera: Apidae). - Hinojosa-Diaz, Ismael A.; Engel, Michael S. (Contributions to Entomology = Beiträge zur Entomologie, 2007)
Two new orchid bees of Euglossa subgenus Euglossella (Apinae: Euglossini) are described and figured from Peru. Both Euglossa (Euglossella) cosmodora sp. n. and E. (E.) urarina sp. n. belong to the decorata species group (i.e., the clade superficially resembling stingless bees of the genus Melipona) of Euglossella and are distinguished from their congeners as well as each other. Keywords Apoidea, Anthophila, Apinae, Euglossini, Peru, taxonomy. Nomenclatural Acts cosmodora Hinojosa-Díaz & Engel, 2007 (Euglossa (Euglossella)), spec. n. urarina Hinojosa-Díaz & Engel, 2007 (Euglossa (Euglossella)), spec. n.